Opportunistic bacterial, viral and fungal infections of the lung - José, Ricardo J. (Medicine (Abingdon), 2020)
Opportunistic infections are a major cause of morbidity and mortality in severely immunocompromised patients, such as those given chemotherapy or biological therapies, and those with haematological malignancy, aplastic anaemia or HIV infection, or recipients of solid organ or stem cell transplants. The type and degree of immune defect dictates the profile of potential opportunistic pathogens; T-cell-mediated defects increase the risk of viral (cytomegalovirus, respiratory viruses) and Pneumocystis jirovecii infections, whereas neutrophil defects are associated with bacterial pneumonia and invasive aspergillosis. However, patients often have combinations of immune defects, and a wide range of other opportunistic infections can cause pneumonia. Importantly, conventional non-opportunistic pathogens are frequently encountered in immunocompromised hosts and should not be overlooked The radiological pattern of disease (best assessed by computed tomography) and speed of onset help identify the likely pathogen(s); this can then be supported by targeted investigation including early use of bronchoscopy in selected patients. Rapid and expert clinical assessment can identify the most likely pathogens, allowing timely appropriate therapy.